THE USES OF RELIGIOUS SYMBOLS TO REPRESENT ISLAM (A Study on Religious Soap Opera “Bukan Islam KTP”) - Sholihati Siti; Heddy Shri Ahimsa Putra; Heru Nugroho (Balai Penelitian dan Pengembangan Agama Semarang, 2016)
This study is entitled “The Uses of Religious Simbols to Represent Islam (A Study on Religious Soap Opera ‘Bukan Islam KTP’)”. The background of the research is based on the facts of the arbitrary use of symbols in representing Islam which are shown on Indonesian televisions. The pattern of the use of religious symbols, either verbal or non-verbal, symbols are generally explicit, but when they are examined using appropriate methods, they actually contains some implicit meanings. The purpose of this study was to discover how Islam is represented on television religious soap pera using religious symbols and to fid out the dominant ideology behind the representation techniques. To analyze the soap operas which consisted of twenty episodes, the researcher used a semiotic approach of John Fiske on television codes. The results of this study are: (1) the use of verbal symbols to represent Islam potentially creates multiple interpretations when they are spoken by different characters, (2) some religious terminologies are often used by antagonist players to express anger and disappointment, (3) the soap opera is dominated by verbal violence used by both protagonist and antagonist players, while antagonist player use violence both in verbal and non-verbal forms. The fidings about ideology embedded in the soap opera are: (1) capitalist-materialistic ideology, (2) ideology of patriarchy, and (3) violence domination.